Morphological Characterization and Conservation Status for the Herbarium Specimens of Orchidaceae in Kurdistan Iraq - Abdulrahman Ahmad, Saman; M.Salih, Rubar; Yaseen Hama, Sakar Y. Hama (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study was contacted on Orchidaceae, it is a second largest family in flowering plants, comes after Asteraceae, and approximately has 25,000–30,000 species in 750–800 genera in the world. This study included 10 genera, Anacamptis (five species), Androrchis (two species), Cephalanthera (one species), Dactylorhiza (three species), Epipactis (two species), Himantoglossum (two species), Limodorum (one species), Neotinea (one species), Ophrys (seven species ), and Orchis (four species). The name abbreviation of authors of plant names follows the International Plant Name Index (IPNI) (https://www.ipni.org/). Images of type collections of most species were checked on virtual herbaria (https://herbarium.univie.ac.at/database/search.php) and JSTOR Global Plants (https://plants.jstor.org/). The taxonomic status, geographical distribution, and the conservation status for all taxa were provided.